Rebuilding Gaza’s health system: A qualitative study of healthcare workers’ experiences and lessons learned from responding to mass casualty incidents (2018–2021) - Anas Ismail; Moatasem Salah; Mads Gilbert; Yousef H. Abu Alreesh; Craig Jones (PLoS ONE, 2026)
Background Gaza has faced numerous military attacks that resulted in mass casualty incidents (MCIs). The ongoing genocide in Gaza has destroyed much of the health system, including killing and injuring of hundreds of health care workers (HCWs). Current thinking on the health system reconstruction lacks empirical data and local HCWs’ perspectives. The study analyses locally driven innovations and lessons learned by HCWs who responded to MCIs between 2018 and 2021 to guide current and future planning of the reconstruction of the health system in Gaza. Methods This was a qualitative study using online and face-to-face interviews with HCWs who responded to the Great March of Return and the 2021 Israeli military attacks. Transcripts and extensive notes from the interviews were recorded and analyzed on NVivo using thematic content analysis. We used the health system building blocks as themes for deductive analysis with a seventh place-based theme (Gaza-specific) to account for the context of Gaza and the MCIs. Results Problems faced by HCWs mostly related to the nature and complexity of traumatic injuries, shortages in HCWs, particularly specialist doctors, poor coordination among actors, duplication of services, and shortages of supplies and equipment. Locally driven innovations and solutions included establishing new services centers, opening and expanding training programs, starting new coordination bodies, and task shifting of staff and facilities. Lessons learned included strengthening training and employment opportunities for staff, enhancing emergency preparedness and capacities, maintaining coordination bodies, enhancing community engagement and strengthening the governance of the Ministry of Health. Conclusion Reconstruction of Gaza’s health system needs to be grounded in its political context and in the experiences of HCWs who have worked in and managed the system. Locally driven solutions and lessons learned can ensure that reconstruction serves as a vehicle for self-determination and sovereignty, rather than entrenching dependency.